2001
DOI: 10.1074/jbc.m009533200
|View full text |Cite
|
Sign up to set email alerts
|

On the Stringent Requirement of Mannosyl Substitution in Mannooligosaccharides for the Recognition by Garlic (Allium sativum) Lectin

Abstract: The kinetics of the binding of mannooligosaccharides to the heterodimeric lectin from garlic bulbs was studied using surface plasmon resonance. The interaction of the bound lectin immobilized on the sensor chip with a selected group of high mannose oligosaccharides was monitored in real time with the change in response units. This investigation corroborates our earlier study about the special preference of garlic lectin for terminal ␣-1,2-linked mannose residues. An increase in binding propensity can be direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…The obtained Ka values were on the order of 10 4 M 21 (b-globulin subpeaks to Gen) or 10 3 M 21 (a-globulin to Lac). These orders were reasonable compared to the reported Ka values for carbohydrate-protein interaction [23][24][25][26].…”
Section: Search For Disaccharide-binding Serum Proteinssupporting
confidence: 69%
“…The obtained Ka values were on the order of 10 4 M 21 (b-globulin subpeaks to Gen) or 10 3 M 21 (a-globulin to Lac). These orders were reasonable compared to the reported Ka values for carbohydrate-protein interaction [23][24][25][26].…”
Section: Search For Disaccharide-binding Serum Proteinssupporting
confidence: 69%
“…QR-2 shows roughly 2.2 times the specific hemagglutination activity of QR-1. It is of interest to note here that the well-characterized garlic lectin ASA I has roughly twice the specific hemagglutination activity of ASA II [37,38]; these groups also found that methyl-α-D-mannopyranoside/mannose showed a similar trend in inhibition of hemagglutination for ASA I and ASA II. Based on the results of hemagglutination activity and SDS-PAGE pattern, it can be speculated that the ImPs QR-1 and QR-2 (occurring in a ratio of 1:4 by weight) are identical to ASA II and ASA I, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Based on the results of hemagglutination activity and SDS-PAGE pattern, it can be speculated that the ImPs QR-1 and QR-2 (occurring in a ratio of 1:4 by weight) are identical to ASA II and ASA I, respectively. Garlic lectins (or agglutinins) belong to the monocot mannose-specific class of lectins, which have strict specificity for terminal or core mannosyl residues [37][38][39]. The garlic bulb agglutinins, ASA I and ASA II are dimeric proteins of 25 kD possessing hemagglutination property.…”
Section: Discussionmentioning
confidence: 99%
“…Glycan binding ability of lectins has been established by several methods like inhibition of agglutination, enzyme-linked lectin adsorbent assay, surface plasmon resonance (SPR), isothermal titration calorimetry and glycan array [7,11,18,85]. X-ray diffraction experiments, used for the three-dimensional structures analysis of several plant lectins, have also contributed in the study [15].…”
Section: Role Of Glycans In Receptors-lectins Interaction and Insectimentioning
confidence: 99%